A predictive model for early clinical diagnosis of spinal tuberculosis based on conventional laboratory indices: A multicenter real-world study - Hu, Xiaojiang; Zhang, Guang; Zhang, Hongqi; Tang, Mingxing; Liu, Shaohua; Tang, Bo; Xu, Dongcheng; Zhang, Chengran; Gao, Qile (Frontiers in Cellular and Infection Microbiology, 2023)
Background Early diagnosis of spinal tuberculosis (STB) remains challenging. The aim of this study was to develop a predictive model for the early diagnosis of STB based on conventional laboratory indicators. Method The clinical data of patients with suspected STB in four hospitals were included, and variables were screened by Lasso regression. Eighty-five percent of the cases in the dataset were randomly selected as the training set, and the other 15% were selected as the validation set. The diagnostic prediction model was established by logistic regression in the training set, and the nomogram was drawn. The diagnostic performance of the model was verified in the validation set. Result A total of 206 patients were included in the study, including 105 patients with STB and 101 patients with NSTB. Twelve variables were screened by Lasso regression and modeled by logistic regression, and seven variables (TB.antibody, IGRAs, RBC, Mono%, RDW, AST, BUN) were finally included in the model. AUC of 0.9468 and 0.9188 in the training and validation cohort, respectively. Conclusion In this study, we developed a prediction model for the early diagnosis of STB which consisted of seven routine laboratory indicators.